Hubungan Frekuensi Konsumsi Fast Food dan Status Gizi Dengan Siklus Menstruasi pada Mahasiswi FIK Universitas Muhammadiyah Surakarta - Aprilia Ananda Widyasari; Muwakhidah Muwakhidah; Listyani Hidayati (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
Irregular menstrual cycles are commonly experienced by adolescent girls and may be influenced by dietary patterns and nutritional status. This study aimed to examine the relationship between fast food consumption frequency and nutritional status with the menstrual cycle among female students of the Faculty of Health Sciences at Universitas Muhammadiyah Surakarta. A cross-sectional design was used with a total sample of 129 respondents selected proportionally from each study program. Data were collected using a Food Frequency Questionnaire (FFQ), nutritional status measurements based on Body Mass Index (BMI), and a menstrual cycle questionnaire. Data analysis was conducted using the Chi-Square test. The results showed no significant relationship between fast food consumption frequency and menstrual cycle (p = 0.351), but a significant relationship was found between nutritional status and menstrual cycle (p = 0.000). It is concluded that nutritional status influences menstrual cycle regularity, while fast food consumption frequency does not have a significant association.